The transformation and the ownership structure in Hungary - Botos Katalin (Proceedings of the Challenges for Analysis of the Economy, the Businesses, and Social Progress : International Scientific Conference Szeged, November 19-21, 2009, 2010)
Was there a transition at all in Hungary? Did the system changed at all in 1990? The answer of the author is yes. Not in the sense that from the society’s top became bottom- as during the transformation after 1945- but in the sense that private property became again to be the basic feature of the economic system. We can follow the evolution of the economy in the mirror of the financial accounts. The players of the market, households, state and financial and non financial enterprises have changed their financial account positions during the period 1990-2006 markedly. The study based on HNB data follows carefully the changes in the asset and liability structures of households, state and enterprises and the financing capacity of each sector. The state’s asset position has diminished, the households’ has grown. But the great winner is the foreign owner’s sector. It has an influence on the per capita GDP and GNI creating a marked difference between them. It is very important to have internal financing capacity because state budget has a deficit since decades. We don’t have enough in the household sector therefore the country needs external financing. The study examines the roots of the international indebtedness of the country, the role of the economic policy and the banking sector’s strategy (selling foreign-financed mortgage loans to the households). Today the state is in a much worse situation than before transition: State debt (and foreign debt of the country) is even higher than in 1990 and state’s ownership (covering the national debt) is now on a minimum level.